Perspectives on Complementation
XV, 252 p.
Keywords: This book presents the latest work in the field of complementation studies. Leading scholars and upcoming researchers in the area approach complementation from various perspectives and different frameworks, such as Cognitive Grammar and construction grammars, to offer a broad survey of the field and provide thought-provoking reading.